Pengaruh Penyuluhan Gizi Terhadap Peningkatan Kebiasaan Membawa Bekal Pada Anak SDN 97 Kendari - Aisa, Wa Ode Siti; Demmalewa, Jenny Qlifianti; Ihsan M, Habib (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2023)
The habit of bringing lunch to school is an important factor in efforts to fulfill children's nutrition to support the nutritional status of school children. The survey results at the Kendari 97 State Elementary School showed that 56% of children did not bring lunch. This study aims to determine the effect of nutrition counseling on increasing the habit of carrying supplies in elementary school children 97 Kendari. This research is a quantitative research (experimental) with a one group pre-test-post-test design. The population is all students in grades V and VI who do not bring supplies at the 97 Kendari State Elementary School in 2022 as many as 43 people and a sample of 43 people obtained by total sampling. The data of this study were obtained by means of observation. Data were analyzed using the Wilcoxon sign rank test. The results showed that before being given nutrition counseling (pre test) the average score of the habit of bringing lunch was 0.83. The results of the Wilcoxon sign rank test obtained a p value of 0.000. The conclusion of this study is that there is an effect of nutrition education on increasing the habit of carrying supplies in elementary school children at 97 Kendari. Suggestions for the Kendari 97 State elementary school to require Kendari 97 State elementary school children to bring supplies every day and routinely conduct nutrition counseling at least once a week and provide rewards to elementary school children who routinely bring supplies and punishment to elementary school children who do not bring supplies.